Exploring the experiences of designing and managing cooking online training during the Covid-19 pandemic - Yong, Yit Hiong; Abdul Wahat, Nor Wahiza; Omar, Diyana Syazana; Hadi, Hasbul; Karunamurthi, Kalaiselvi; Li, Xiao Yan; Husin, Mohd Ashrof; Mohammad Sohami, Noor Hafida; Roslan, Nor Ilanah; Mohd Arifin, Norshahana; Yi, Qin; Hanwen, Wang (Human Resource Management Academic Research Society, 2020)
A group of graduate students was assigned to design and conduct training as their group project. Nevertheless, the whole world, including Malaysia was hit by the Covid-19 pandemic. Everyone in the country was under the first phase of the Movement Control Order (MCO). Hence, face-to-face training was not a viable option. Alternatively, the students had to conduct online training. The assignment was the first-time experience for them to design and provide training. A question arose on how well the graduate students' experience was in designing, implementing, and evaluating online training. This article presents a qualitative study on implementing an online training program titled "Learning How to Make Halal Chinese Dumplings Online!" by graduate students in the Training Design and Management course at Universiti Putra Malaysia. This study aimed to explore the design and implementation of the online training program. Data collection was through an online focus group discussion (FGD) involving 11 respondents and a document analysis of a written report by the training implementers. The central theme that emerged from the data analysis is training design for online training. Meanwhile, the sub-themes are as follows: (a) training needs analysis and rationale for online training in making halal Chinese dumplings, (b) training design, (c) training evaluation, and (d) challenges in conducting online training. Methodologically, this study implies the feasibility of successful data collection via online platforms. The findings on the well-designed and implemented online training based on training needs analysis and continuous evaluation suggested that we could still gain access to the ocean of knowledge via formal or informal online learning and education programs at a challenging time of Pandemic Covid-19.